2008
DOI: 10.1016/j.exphem.2007.11.009
|View full text |Cite
|
Sign up to set email alerts
|

In vivo selection of hematopoietic stem cells transduced at a low multiplicity-of-infection with a foamy viral MGMTP140K vector

Abstract: Objective-Using a clinically relevant transduction strategy, we investigated to what extent hematopoietic stem cells in lineage-negative bone marrow (Lin neg BM) could be genetically modified with a FV vector that expresses the DNA repair protein, O 6 -methylguanine DNA methyltransferase (MGMT P140K ) and selected in vivo with submyeloablative versus myeloablative alkylator therapy.Methods-Lin neg BM was transduced at a low multiplicity-of-infection (MOI), with the FV vector, MD9-P140K, that co-expresses MGMT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 53 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…44 Here, magselectofection with low MOIs (Յ 3) yielded up to 50% transduced cells ( Figure 4) compared with only 9.5% with an MOI of 5 to 8 using a standard transduction protocol for Lin Ϫ BM cells as reported previously. 45 Importantly, the magselectofected cells were fully competent in colony-forming assays ( Figure 4B-C), and administration in mice also resulted in long-term stable reconstitution and long-term GFP expression ( Figure 4D-F).…”
Section: Discussionmentioning
confidence: 99%
“…44 Here, magselectofection with low MOIs (Յ 3) yielded up to 50% transduced cells ( Figure 4) compared with only 9.5% with an MOI of 5 to 8 using a standard transduction protocol for Lin Ϫ BM cells as reported previously. 45 Importantly, the magselectofected cells were fully competent in colony-forming assays ( Figure 4B-C), and administration in mice also resulted in long-term stable reconstitution and long-term GFP expression ( Figure 4D-F).…”
Section: Discussionmentioning
confidence: 99%
“…After one week, 20 colonies were picked for each mouse and subjected to standard LM-PCR analysis for identifying the location of the provirus in the genome. As described previously, 46 the position of the transgene from each colony was evaluated using the SeqMap website (http://seqmap.compbio.iupui.edu) and confirmed using the http://genome.ucsc.edu and http://www.ensembl.org websites. From each mouse, one proviral integration was detected (Table 2).…”
Section: Evaluation Of Proviral Integrantsmentioning
confidence: 99%
“…45 The DNA from excised bands was cloned into pCR2.1 using the TOPO cloning kit (Invitrogen, Frederick, MD) and then sequenced on an ABI Gene Amp 3770 System (Applied Biosystems, Foster City, CA). As described previously, 46 SeqMap (http://seqmap.compbio.iupui.edu, Indiana University School of Medicine) was used to map the sequences against the mouse genome. This was then confirmed by mapping the positions using the Ensembl website (http://www.ensembl.org) and mus musculus database release 42, December 2006, 47 and the UCSC Genome Browser (http://genome.ucsc.edu).…”
Section: Ligation-mediated Polymerase Chain Reactionmentioning
confidence: 99%
“…(Beard et al, 2010;Neff et al, 2005) Numerous transplant studies have convincingly proven that long-term repopulating murine HSCs could be selected in vivo with O 6 -BG/BCNU, O 6 -BG /TMZ, or O 6 -BG /CCNU. (Cai et al, 2008;Davis et al, 2004;Jansen et al, 2002;Kreklau et al, 2003;Milsom et al, 2004;Persons et al, 2003;Persons et al, 2004;Ragg et al, 2000;Sawai et al, 2003;Sawai et al, 2001) In regards to modeling of this approach with human HSPCs, we and others previously demonstrated that MGMT P140K -transduced SCID-repopulating cells and their progeny could be selected in vivo in NOD/SCID mice. Human HSPCs derived from umbilical cord blood (UCB) or granulocyte colony-stimulating factormobilized peripheral blood (MPB) that expressed MGMT P140K could be selected in vivo by www.intechopen.com nonmyeloablative doses of O 6 -BG and BCNU.…”
Section: In Vivo Selection Of Hspcs In Humanized Mouse Modelsmentioning
confidence: 99%